Violência de gênero: um estudo de processos criminais de estupro em Uberlândia - 1940/1960 - Coelho, César Castro e (2007)
The purpose of this essay is to reckon about this violence of a gender, particularly about the crimes of rape in the city of Uberlândia between the decades of 1940 to 1960. This argument concerns about how this theme is showing its importance on the fields of history lately. Decomposing women´s paradigm of being lower than men, providing a better view on social relationships involving them. This project began from the research of several criminal trials that had been incinerated from Abelardo Penna Forum for lack of room. They are about 20.000 trials dating from 1890 to 1984 that can be found nowadays at CDHIS (Centro de Documentação e Pesquisa em História History Center of Documentation and Research) of Uberlândia Federal University. In this documentation we found information about the social subjects involved, for instance: names, professions, education, age, ethnicity, marital status, addresses, nationality and social rates. We were also allowed to check on the victims` speeches, as well as the defendants, judges, promoters, the commission agents, doctors, lawyers and witnesses involved in such a crime, what makes the source of this essay. Realizing the great possibilities of analyses on this documentation, the field of reflection used on this research has its goal on working the speeches built by the violence of a gender in Uberlândia City. And understand how culturally such a pattern behavior of femininity and masculinity were built in the Brazilian society, having as a reference the jurisprudence of this remote time, and mainly the Civil Code from 1916 and the Criminal Code from 1940.